COMMENTS OF FETAL HEART RATE CHART DURING THE LABOR AT THE DEPARTMENT OF OBSTETRICS AND GYNECOLOGY, NGHE AN PEDIATRICS AND OBSTETRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe normal and abnormal fetal heart rate charts in labor and the infant status ofsuch cases.Subjects-methods: Cross-sectional description 1035 women with a gestational age of 36 weeks ormore in labor receive obstetric monitoring at Nghe An Obstetrics and Pediatrics Hospital.Result: 212 cases had abnormal fetal heart rate charts, of which 19.8% of newborns had an Apgarindex < 7 points. When the types of fetal heart rate decrease combined with the 0 fluctuations, thepercentage of babies born with Apgar index < 7 points increased from 18.66 to 63.86 times. Cesareansection treatment had the highest rate of 63.48%. The percentage of infants with an Apgar index
Keywords: Continuous fetal heart rate chart.